The impact of accent stigma on self-efficacy and acculturation strategy among international students in the United States - Yan, Xiaodi (Frontiers in Psychology, 2024)
Introduction This paper aimed to understand international students’ experience of accent stigma during interpersonal interactions, and how it affected their self-efficacy and acculturation strategy during intercultural adjustment. Methods Study 1 conducted in-depth interviews with 15 international students (60% female, 21.6 years old on average), asking for narratives on how they perceived accent stigma was enacted in everyday scenarios. Study 2 distributed a survey to 132 international students (53.5% female, 25.52 years old on average) with scales measuring perceived accent stigma, perceived discrimination, perceived hate, fear, self-efficacy, and integration into the host culture. Results Based on thematic analysis, Study 1 identified verbal disapproval, verbal avoidance, nonverbal disapproval, and nonverbal avoidance as four behavioral markers that signal the enactment of accent stigma during interpersonal interactions. Study 2 assessed a path model and found that accent stigma was associated with more perceived discrimination, perceived hate, and fear. Accent stigma also had negative impacts on self-efficacy, which in turn, resulted in poor integration into the host culture. Conclusion This study examined the negative consequences of accent stigma on international students and highlighted the role of self-efficacy during international students’ intercultural adjustment. Findings had important theoretical and practical implications in terms of better supporting and serving international students during their stressful transitional period in a new culture